Identification and evaluation of midbrain specific longevity-related genes in exceptionally long-lived but healthy mice - Kim, Hyojung; Huh, Yu-Jin; Kim, Ji Hun; Jo, Minkyung; Shin, Joo-Heon; Park, Sang Chul; Ahn, Jee-Yin; Lee, Yun-Il; Lee, Yunjong (Frontiers in Aging Neuroscience, 2023)
Brain aging is a complex biological process that is affected by both genetic background and environment. The transcriptomic analysis of aged human and rodent brains has been applied to identify age-associated molecular and cellular processes for which intervention could possibly restore declining brain functions induced by aging. However, whether these age-associated genetic alterations are indeed involved in the healthy aging of the brain remains unclear. We herein characterized a naturally occurring, extremely long-lived (34 months of age) but healthy mouse group retaining well-preserved motor functions. Strikingly, these long-lived mice maintained tyrosine hydroxylase expression and dopaminergic fiber densities, even in the presence of persistent neuroinflammation and expression of aging markers. Combined with Endeavor gene prioritization, we identified the following midbrain-specific longevity-associated genes in the midbrain of these mice: aimp2, hexb, cacybp, akt2, nrf1, axin1, wwp2, sp2, dnajb9, notch, traf7, and lrp1. A detailed biochemical analysis of the midbrain of these long-lived mice confirmed the increased expression of Nrf1 and the activation of Akt1 and 2. Interestingly, dopaminergic neuroprotective and age-associated E3 ubiquitin ligase parkin expression was retained at high levels in the aforementioned midbrains, possibly supporting the suppression of its toxic substrates AIMP2 and PARIS. In contrast, the 24-month-old mice with dopaminergic neurite deficits failed to maintain parkin expression in the midbrain. AIMP2-induced cytotoxicity, mitochondrial stress, and neurite toxicity can be prevented by overexpression of parkin, Akt1, and Nrf1 in SH-SY5Y and PC12 cells, and basal expression of parkin, Akt1, and Nrf1 is required for maintenance of mitochondrial function and neurite integrity in PC12 cells. Taken together, this longevity-associated pathway could be a potential target of intervention to maintain nigrostriatal dopaminergic fibers and motor ability to ensure healthy longevity.